EFFECT OF ELECTRONIC WORD OF MOUTH (E-WOM) ON VISITING INTENTION MEDIATED BY DESTINATION IMAGE AT THE RAWA BENTO TOURISM OBJECT - Haryono, Gampo; Albetris, Albetris (Journal of Business Studies and Management Review, 2024)
This research aims to examine the effect of E-WOM on visiting intention mediating destination image at the Rawa Bento tourist attraction. The data used in this research are primary data and secondary data. The research period starts from April to August 2023. The sampling technique used is non-probability sampling with a purposive sampling method. The sample size in this study refers to the sampling formula from Hair et al (2010), with sixteen statements as indicators, so the sample size is 90 respondents. This research uses a quantitative approach with data processing and analysis using SEM PLS analysis namely Smart PLS. The research results show that E-WoM on destination image has no effect, E-WoM on visiting intention has no effect. Destination image has a significant effect on visiting intention. E-WOM (Electronic Word of Mouth) on visiting Intention mediated Destination Image has no effect.